Pengaruh Inflasi, PDRB, dan Upah Minimum Provinsi terhadap Penyerapan Tenaga Kerja di Indonesia - Sang Ketut Ari Ardiawan; Made Suyana Utama (Universitas Veteran Bangun Nusantara, 2024)
Population growth in Indonesia is getting bigger and bigger, the increasing population in Indonesia has an impact on increasing the number of workers. The total population of Indonesia in 2022 is 275,773,800 people spread across various provinces, the number of working-age people in 2022 is 209,420,383 people spread across various provinces, the number of labor force in 2022 is 143,722,644 people spread across various provinces, and the number of working population in 2022 is 135,296,713 people spread across various provinces. If the amount of labor exceeds market demand, it can lead to unemployment problems which will increase the probability of poverty, and socio-economic phenomena in society such as crime and other phenomena. This study aims to determine how the influence of three factors that theoretically have an influence on labor absorption. The three factors are inflation, Gross Regional Domestic Product (GRDP), and Provincial Minimum Wage. The data used is panel data for five years, from 2018-2022. The data analysis technique used is panel data analysis with the EViews application. The results showed that simultaneously the variables of inflation, gross regional domestic product, and provincial minimum wage had a positive and significant effect on employment in provinces in Indonesia in 2018-2022, and partially the variables of inflation, gross regional domestic product, and provincial minimum wage had a positive and significant effect on employment in provinces in Indonesia in 2018-2022.